1901 Cal. Stat. Laws 476, § 179 - (:unkn) unknown (General Publisher, 1901)
Prohibited the use of a shotgun of larger calibur known as a ten gauge. Violators guilty of a misdemeanor. Possession in the field, on marsh, bay, lake, or stream shall be prima facie evidence of its illegal use.
--
Keywords: CALIBER RESTRICTION